2009
DOI: 10.1590/s1806-37132009001000005
|View full text |Cite
|
Sign up to set email alerts
|

Empilhamento de ar e compressão torácica aumentam o pico de fluxo da tosse em pacientes com distrofia muscular de Duchenne

Abstract: Objective: To evaluate cough efficiency using two manually-assisted cough techniques. Methods: We selected 28 patients with Duchenne muscular dystrophy. The patients were receiving noninvasive nocturnal ventilatory support and presented FVC values < 60% of predicted. Peak cough flow (PCF) was measured, with the patient seated, at four time points: at baseline, during a spontaneous maximal expiratory effort (MEE); during an MEE while receiving chest compression; during an MEE after air stacking with a manual re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 20 publications
0
20
0
4
Order By: Relevance
“…However, we did not determine how frequently the maneuver was performed or the influence of the maneuver on pulmonary parameters. The “air stacking” maneuver is reported to have positive effects only in peak flow of cough and maximum insufflation capacity [22,23]. The CVF continued to decline independently of the use of this maneuver [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not determine how frequently the maneuver was performed or the influence of the maneuver on pulmonary parameters. The “air stacking” maneuver is reported to have positive effects only in peak flow of cough and maximum insufflation capacity [22,23]. The CVF continued to decline independently of the use of this maneuver [23].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there was no increase in the CPF in four patients with respiratory muscle weakness with scoliosis, although there was an increase in the patients with respiratory muscle weakness without scoliosis (Sivasothy et al 2001, Chatwin et al 2003. In contrast, a small study in patients with Duchenne muscular dystrophy did not show a significant difference between the patients who had kyphoscoliosis and those who did not, although this was again a study with higher risk of bias (Brito et al 2009).…”
Section: Patients With Chronic Obstructive Pulmonary Disease and Indimentioning
confidence: 73%
“…This improvement is higher compared to assisted inspiration techniques alone and lower than when the techniques of assisted inspiration and expiration are combined. A study in 28 patients with Duchenne muscular dystrophy showed that CPF (mean ± SD) is higher with the combination of the MAC with manual hyperinflation using a resuscitation bag (292±86 l/min), compared to the techniques alone, MAC (231±81 l/min), hyperinflation (225±80 l/min), and unassisted cough (171±67 l/min) (Brito et al 2009). In mechanically ventilated patients, CPF was also higher when MAC was applied with an increased positive end-expiratory pressure and inspiratory time compared to MAC alone (112.3±15.6 l/min versus 95.8±18.3 l/m, p <0.05) (Silva et al 2012).…”
Section: Assisted Expirationmentioning
confidence: 99%
“…These authors found that the decrease in lung volume after surgery was smaller in the patients treated with breath stacking and that this maneuver allowed greater lung expansion and greater maintenance of inspiratory volume. Breath stacking has also been proposed, in a modified form using a manual resuscitation bag, a one-way valve and a mask or mouthpiece, to increase the maximum inspiratory capacity and expiratory flow to improve cough in patients with neuromuscular disorders or spontaneously breathing intubated [32][34].…”
Section: Discussionmentioning
confidence: 99%